Differential expression of serum proteome of hypercholesterolemic rats following treatment with Ficus deltoidea / Chuo Peck Ham - Chuo , Peck Ham (2018)
Cardiovascular disease (CVD) is one of the most common noncommunicable disease resulting in cardiac dysfunction and heart failure. In Malaysia, hypercholesterolemia or high blood cholesterol has emerged as the main risk factor for CVD. Currently, there is a paradigm shift of interest towards Eastern medicines as alternative approaches in prevention and therapeutic treatment for cholesterol lowering and cardioprotection. Ficus deltoidea (Mas Cotek) is amongst the medicinal plants traditionally consumed either as prevention or self-medication for various diseases like high blood pressure, diabetes and high blood cholesterol. This current study utilized proteomic application in determining the changes in series of proteins that are being differently expressed in response to F. deltoidea treatment in hypercholesterolemic and cardiac damaged–carbon tetrachloride (CCl4) induced rats. Identification and quantification of proteins were conducted using relative quantitative techniques, such as 2D-GE along with Progenesis Samespots image analysis software and MALDI ToF/ToF mass spectrometry. Our study demonstrated a significant alteration of protein abundances following F. deltoidea treatment with the majority of these identified proteins were involved in lipid metabolism and transport, inflammation and immune response, anti oxidant protein, acute phase protein, cholesterol homeostasis and cholesterol binding as well in cytoskeletal and structural effects. The hypercholesterolemic related proteins (Apo A1, Apo E, RBP4, HAP, PDE1, C3, C1s, PROM1, TTR, MUP, CPI and PLG) identified are the key proteins responsible for the suppression of hypercholesterolemia following treatment with F. deltoidea extracts. Consequently, TPM2, MYH6, SUMO3, Apo A1 and Apo E are associated with cardioprotective effects. Interestingly, Apo E and Apo A1 are the two profound putative proteins that exhibit both cholesterol lowering and ameliorate cardioprotection effects. The variations of these proteins may provide valuable new molecular insights into the mechanism of cholesterol lowering and cardioprotective effects of F. deltoidea. We speculated that long-term F. deltoidea consumption would set-back further extent of cardio atherosclerosis and myocardial infarction, as well subsequent cardiac function deterioration and mortality in hypercholesterolemic subjects. Thus, further development of this study will enable the finding of alternative treatments as well as preventions for CVD.